Emotions of CLIL Preservice Teachers in Teaching Non-Linguistic Subjects in English - Lucía Belmonte Carrasco; Guadalupe de la Maya Retamar (Universidad Nacional de Colombia, 2023)
This paper reports an exploratory, descriptive study on the emotions of content and language-integrated learning preservice teachers. The study, carried out in a Spanish university, aimed at analysing the internship experience of 19 preservice teachers in the context of a master's degree in bilingual education (Spanish-English) for primary and secondary school teachers to determine the emotions experienced and the causative factors. The participants completed a questionnaire which showed that positive emotions were more frequent than negative ones. The variable causing such feelings included the subject taught, the sex of the teaching staff, previous experience, attitudes of educational centre tutors, and the students themselves. Therefore, the study highlights the affective dimension of teaching content and language-integrated learning.